2015
DOI: 10.3892/mmr.2015.3288
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Fanconi anemia genes FANCD2 and FANCF in the molecular basis of drug resistance in leukemia

Abstract: The Fanconi anemia (FA)‑associated proteins FANCF and FANCD2 are important components of the FA pathway of DNA crosslink repair. FANCF and FANCD2 have been found to be involved in drug‑resistant multiple myeloma, ovarian cancer, non‑small‑cell lung cancer, and head and neck cancer. However, it is unclear whether these two genes participate in adriamycin (ADR)‑resistant leukemia. Therefore, the aim of the current study was to investigate FANCF and FANCD2 expression in drug‑resistant and drug‑sensitive leukemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The ADR doses used in vitro were dependent on the survival of the K562 and K562/ADR cells. According to the results of previous experiments by the authors, pre-treatment with ADR at 2 µM consistently enhanced toxicity in K562 cell lines but not in K562/ADR cell lines (11). Therefore, 2 µM ADR and 5 µM Olaparib were selected for use in further experiments.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The ADR doses used in vitro were dependent on the survival of the K562 and K562/ADR cells. According to the results of previous experiments by the authors, pre-treatment with ADR at 2 µM consistently enhanced toxicity in K562 cell lines but not in K562/ADR cell lines (11). Therefore, 2 µM ADR and 5 µM Olaparib were selected for use in further experiments.…”
Section: Discussionmentioning
confidence: 67%
“…Previously published studies by the authors have revealed that the Fanconi anemia (FA)/BRCA signaling pathway is involved in the acquired ADR resistance of leukemia cells (11), and that extensive crosstalk exists within the DNA repair pathway (12). PARP1 inhibitors can strengthen DNA damage when combined with traditional chemotherapy drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, unsupervised clustering was performed with scRNA-seq data from patient B using the SC3 pipeline (version 1.12.0) (19). The functions of DGEs were determined through a literature review (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)…”
Section: Gene Fusion Predictionmentioning
confidence: 99%
“…Patients with a disrupted structure of FANCD2, mainly carriers of Fanconi anemia, have higher risk of cancer development [64,65]. The most frequent cancer types related to FANCD2 are ovarian [66], hepatic [67], lung [68], breast cancer [69] and leukemia [70]. FANCD2 co-localizes with RAD51a following DNA damage is an indication that FANCD2 and RAD51a share roles in DNA repair through physical interactions [16,17,71].…”
Section: In Silico Model For the Rad51a Interaction With Fancd2mentioning
confidence: 99%